Surface stoichiometry modification and improved DC/RF characteristics by plasma treated and annealed AlGaN/GaN HEMTs. (March 2018) - Upadhyay, Bhanu B.; Takhar, Kuldeep; Jha, Jaya; Ganguly, Swaroop; Saha, Dipankar
Highlights: A combination plasma treatments and annealing lead to AlGaN surface modification. The modified stoichiometry leads to improved product for mobility and 2DEG density. The plasma treatment and annealed HEMTs show improved DC and RF characteristics. The fT, leakage, sub-threshold slope and other characteristics improve. Abstract: We demonstrate that N2 and O2 plasma treatment followed by rapid thermal annealing leads to surface stoichiometry modification in a AlGaN/GaN high electron mobility transistor. Both the source/drain access and gate regions respond positively improving the transistor characteristics albeit to different extents. Characterizations indicate that the surface show the characteristics of that of a higher band-gap material like Al x O y and Ga x O y along with N-vacancy in the sub-surface region. The N-vacancy leads to an increased two-dimensional electron gas density. The formation of oxides lead to a reduced gate leakage current and surface passivation. The DC characteristics show increased transconductance, saturation drain current, ON/OFF current ratio, sub-threshold swing and lower ON resistance by a factor of 2.9, 2.0, 10 3.3, 2.3, and 2.1, respectively. The RF characteristics show an increase in unity current gain frequency by a factor of 1.7 for a 500 nm channel length device.